TANTANGAN PESANTREN DALAM KOMERSIALISASI PENDIDIKAN DI TENGAH GLOBALISASI - Sholehuddin Sholehuddin (Lentera Pendidikan : Jurnal Ilmu Tarbiyah dan Keguruan, 2012)
This adult education including schools facing the challenge of globalization, which results insilaisasi komer education. In this era of human tradition to main-tain their existence through education included in its schools received a serious challenge, because education too real for some people used to accumulate tal ca-pitalization and profits. Education used as a commodity and not all people can access it. It is this fact that must be faced by the schools were able to provide the required service quality education at a low cost. Pesantren there was the ins-titution grow and develop in society and become a driving force of community itself, by him that, when the cost of education in schools is expensive or difficult to reach, then schools will alienate them from society.